2020
DOI: 10.1002/ecs2.3033
|View full text |Cite
|
Sign up to set email alerts
|

Flea sharing among sympatric rodent hosts: implications for potential plague effects on a threatened sciurid

Abstract: For vector‐borne diseases, the abundance and competency of different vector species and their host preferences will impact the transfer of pathogens among hosts. Sylvatic plague is a lethal disease caused by the primarily flea‐borne bacterium Yersinia pestis. Sylvatic plague was introduced into the western United States in the early 1900s and impacts many species of rodents. Plague may be suppressing populations of the threatened northern Idaho ground squirrel (Urocitellus brunneus) if a competent flea communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…Several ectoparasites (e.g., Rhipicephalus sp, Xenopsylla sp 1) showed a wider host range, presumably due to their ability to infect multiple locally available hosts [61]. These results are consistent with previous studies and indicate that host sharing among vectors is more common than previously believed [62]. Such non-specific host-ectoparasite associations can facilitate transmission of several pathogens, making their ecology a crucial part of vectorborne pathogen dynamics [63].…”
Section: (B) Bartonella Prevalence and Spillover May Be Mediated By E...supporting
confidence: 87%
See 1 more Smart Citation
“…Several ectoparasites (e.g., Rhipicephalus sp, Xenopsylla sp 1) showed a wider host range, presumably due to their ability to infect multiple locally available hosts [61]. These results are consistent with previous studies and indicate that host sharing among vectors is more common than previously believed [62]. Such non-specific host-ectoparasite associations can facilitate transmission of several pathogens, making their ecology a crucial part of vectorborne pathogen dynamics [63].…”
Section: (B) Bartonella Prevalence and Spillover May Be Mediated By E...supporting
confidence: 87%
“…Rhipicephalus sp , Xenopsylla sp 1 ) showed a wider host range, presumably due to their ability to infect multiple locally available hosts [73]. As observed elsewhere [74], host sharing was the predominant pattern observed in the community. Such generalist ectoparasites can facilitate the transmission of pathogens between hosts [75], making their ecology a crucial part of vector-borne pathogen dynamics.…”
Section: Discussionmentioning
confidence: 85%
“…Also, at lower elevations, the forest and thick grass could be harmful to plague hosts, while at higher elevations, there would be lack of food (Qian et al 2014). The shared distribution of rodents, fleas, and human beings increases the danger of infection and epidemic potential of the plague, especially for farmers who live within the higher probability areas (Nyirenda et al 2017;Goldberg et al 2020), such as those identified in our map.…”
Section: Discussionmentioning
confidence: 91%
“…8000 g) and a much smaller Phodopus sungorus (average body mass 33.2 g). Mean abundance attained by fleas on a host may or may not correlate positively with host size (Kiffner et al, 2013;Goldberg et al, 2020). No study that aims to test the effect of a host's BMR on flea abundance has been performed, but indirect evidence suggests that this effect is unlikely.…”
Section: Host Traits: Physiologymentioning
confidence: 99%